Penelusuran Mekanisme Molekuler Peningkatan Sensitivitas Sel MCF-7/DOX Terhadap Doxorubicin Oleh Naringenin Melalui Regulasi Ekspresi P-Glikoprotein Dan Interaksinya Pada Protein Kinase - , DYANINGTYAS DEWI PAMUNGKAS PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Naringenin, an abundant flavanon in the peel of citrus fruits is reported to possess anti-proliferative effect in many cancer cells. Herein, we investigated the cytotoxic effect and apoptosis induction of naringenin in combination with doxorubicin on MCF-7/DOX cells to increase sensitivity of doxorubicin. The cytotoxicity assay of naringenin alone and combination with doxorubicin were carried out by using MTT assay. Cell viability and combination index were used as the parameters to evaluate combination effectiveness. Apoptosis assay was done using double staining method using Ethidium Bromide- Acridine Orange. Investigation on the expression of P-glycoprotein were determined by immunocytochemistry method. PLANTS and MOE were used to analyze interaction naringenin with protein kinases, EGFR, HER-2, IKK and factin. Naringenin and doxorubicin showed cytotoxic effect on MCF-7/DOX cells with IC50 values of 280 uM (74 Î¼g/ml), respectively. Based on CI values, combination naringenin 90 Î¼M (24 Î¼g/ml) and doxorubicin 230 nM (1.3 Î¼g/ml) was the best synergistic effect. In accordance with the IC50 results, the apoptosis assay of combination treatment indicated increase of apoptotic cells compared than single treatment. Doxorubicin increases the expression of P-glycoprotein on cytoplasm however naringenin might interfere the P-gp localization to membrane cell, resulting inactive P-gp. Based on score docking, naringenin might interfere activation of EFGR, HER-2, IKK and f-actin. These results conclude that naringenin is a potential to increase sensitivity of doxorubicin and decrease resistant effect of doxorubicin and the molecular mechanism of P-gp localization need to be explored.